(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical and anatomical characteristics of a group of patients with total edentulousness who received total removable dentures at the Department of Prosthetics, National Hospital of Odonto-Stomatology, Hanoi. Subjects and methods: A descriptive study was conducted on 34 patients with total edentulousness in both jaws, treated during the period 2023-2025. General characteristics and anatomical features related to prosthetics were recorded at the time before treatment. Results: The average age of the study group was 68.1 ± 15.9; the gender distribution was even. The degree of alveolar bone resorption was mainly moderate. The lower jaw had more unfavorable characteristics compared to the upper jaw in terms of alveolar ridge morphology and arch shape. Conclusion: Patients with total edentulousness were mainly elderly, with many anatomical and functional factors unfavorable for prosthetics, especially in the lower jaw.